Síntese e caracterização das cerâmicas do tipo Ba5Li2W3O15 e suas propriedades dielétricas em micro-ondas e radiofrequência - Souza, Natália Dantas Gomes de (2022)
In recent years, technological development in the area of ceramic materials has attracted the attention of the scientific community due such as applications in microwave (MW) and radiofrequency (RF) devices. Perovskite ceramics have relevant dielectric properties, such as high relative dielectric permittivity (ɛr), low loss tangent (tgδ) and a resonance frequency temperature coefficient (τf) close to ± 10 ppm.°C-1. The present work reports the synthesis of complex perovskite of the Ba5Li2W3O15 type (BLWO) and investigates its dielectric properties applied to electronic devices such as dielectric resonator antennas (DRA). The structural and dielectric properties of BLWO were studied. By X-ray diffraction, the presence of two crystalline phases was identified: Ba5Li2W3O15, with a hexagonal structure, and BaWO4, with a tetragonal structure, also confirmed by the vibrational modes obtained by Raman spectroscopy. Scanning electron microscopy (SEM) the presence of pores was observed, as well as well-defined grains and grain boundaries. The electrical measurements suggest that the samples have a thermoactivated process and their activation energy (Ea) was calculated, being around 1 to 2 eV. The dielectric resonators in MW presented εr between 13 and 15 and tgδ in the range of 1.0x10-3. The measured τf reached values between 17.6 and 6.6, being considered a good result for dielectric ceramics. Some ceramics were tested as an antenna and their far-field parameters were obtained through numerical simulation. The far field parameters of BLWO DRAs showed low gain, efficiency around 97%, good directivity and reflection coefficient (S11) below -10dB, making these ceramics promising in applications such as antennas. The DRAs of this work when compared to commercial antennas show similar values of low gain and high efficiency.